Activity Test Of Methanol And Ethanol Extract Of Reed Leaves (Imperata Cylindrica L.) As An Anti-Inflammatory - Wa Ode Helma; Sarni; Muhammad Tasjiddin Teheni (International Journal of Multidisciplinary Learners, 2024)
The Imperata cylindrica L. It has long been used by Indonesian people as a medicinal plant that has various benefits, including its ability as an anti-inflammatory agent. This plant contains active compounds such as flavonoids, which are believed to have anti-inflammatory effects. The purpose of this study was to evaluate the anti-inflammatory activity of methanol and ethanol extracts of Imperata cylindrica leaves, and to compare the effectiveness of the two extracts. The method used in this study was experimental in the laboratory, with the extraction of Imperata cylindrica leaves using methanol and ethanol solvents. Anti-inflammatory activity was measured in vitro using the UV-Vis spectrophotometry method with bovine serum albumin (BSA) standards at a wavelength of 660 nm. The results showed that the methanol and ethanol extracts of Imperata cylindrica leaves contain compounds that have the potential to have anti-inflammatory activity. Even so, the methanol extract showed weak anti-inflammatory activity with an IC50 value of 194.15 μg/ml. In contrast, the ethanol extract had an IC50 of 209.36 μg/ml, which indicated less significant anti-inflammatory activity. Based on the results of this study, it can be concluded that the extract of cogongrass leaves extracted with methanol has better anti-inflammatory potential compared to ethanol extract, although the effect is still weak. Further research is needed to identify the active compounds responsible for this activity and to improve its therapeutic potential.